The Degree of Linear Polarization for Suspended Particle Fields from Diverse Natural Waters - Zhai, Siyao; Twardowski, Michael (Frontiers in Remote Sensing, 2021)
The particulate Degree of Linear Polarization (DoLP) of waters from six diverse regions around the globe was measured with the custom Multi-Angle Scattering Optical Tool (MASCOT). DoLP here is defined as the ratio of two elements of Mueller scattering matrix, i.e., -M_12/M_11. Field sites covered inland waters, coastal oceans and open oceans, including both ocean color Case I and II water types. The angular shape of the measured particulate DoLP was analyzed in detail for each field site and for the global average. Three parameters used to quantitatively characterize DoLP shape were the symmetry with respect to 90°, peak magnitude, and peak angle of measured DoLP angular curve. Vertical profiles of particulate DoLP were analyzed with maximum recorded depth of 111 m. Converse to Rayleigh scatterers, we found measured particulate DoLPs were not symmetric with respect to 90°. On average, DoLP peaks were shifted slightly toward larger angles, with most falling between 90° and 95°. All particulate DoLP peak magnitudes were less than 1, and generally varied within [0.6, 0.9]. Lorenz-Mie (homogeneous sphere) light scattering theory was used to construct a new inversion for bulk particulate refractive index from a lookup table based on DoLP and spectral attenuation measurements. We compared the Mie-DoLP-based particulate refractive index retrieval with the backscattering-based model from (Twardowski et al. 2001). Particulate refractive index retrieved with the two models were roughly comparable. At two of the six field sites we saw good agreement between the two models, whereas at another two field sites we observed large discrepancies between the two models. Further investigation on the choice of the modeled particle shapes and compositions may improve this retrieval approach. Results are compatible with previous studies on DoLPs in natural waters and comprehensive observations are provided on the particulate DoLP angular shape, vertical profile and global distributions that are important for future vector radiative transfer simulations. This study is relevant to future PACE polarimeters and associated remote retrieval of oceanic particle composition using polarimetry.